Absolute X‐ray energy measurement using a high‐accuracy angle encoder. (8th December 2020) - Masuda, Takahiko; Watanabe, Tsukasa; Beeks, Kjeld; Fujimoto, Hiroyuki; Hiraki, Takahiro; Kaino, Hiroyuki; Kitao, Shinji; Miyamoto, Yuki; Okai, Koichi; Sasao, Noboru; Seto, Makoto; Schumm, Thorsten; et al.
Abstract : Absolute X‐ray energy measurement based on a Bond diffractometer is demonstrated. This diffractometer uses a reference silicon single‐crystal plate and a highly accurate angle encoder to measure the Bragg angle accurately. Abstract : This paper presents an absolute X‐ray photon energy measurement method that uses a Bond diffractometer. The proposed system enables the prompt and rapid in situ measurement of photon energies over a wide energy range. The diffractometer uses a reference silicon single‐crystal plate and a highly accurate angle encoder called SelfA. The performance of the system is evaluated by repeatedly measuring the energy of the first excited state of the potassium‐40 nuclide. The excitation energy is determined as 29829.39 (6) eV, and this is one order of magnitude more accurate than the previous measurement. The estimated uncertainty of the photon energy measurement was 0.7 p.p.m. as a standard deviation and the maximum observed deviation was 2 p.p.m.